Raising Capital to Raise Crops: Slave Emancipation and Agricultural Output in the Cape Colony - Igor Martins (African Economic History Network (AEHN), 2020)
Agricultural output fluctuated worldwide after the emancipation of slaves. The usual explanation is that former slaveholders now lacked labor. This is not the full story: slaves were not just laborers but capital investments to support production. Using databases covering more than 40 years from Stellenbosch in the British Cape Colony, this study measures changes in output before and after emancipation to determine the role of slaves as factors of production. Large shortfalls in compensation paid to slaveholders after the 1833 Abolition Act reveal that slaves were a source of capital that strongly influenced production levels, an important reason for the output variation.
Keywords: J47; N37; N47; N57; 330; slave emancipation; slave trade; agricultural history; labor coercion; Cape Colony